LANGUAGE CONSCIOUSNESS AS AN INDICATOR OF INTEGRATION CONSCIOUSNESS - Gulnoz, Muratova (Журнал иностранных языков и лингвистики, 2021)
This article is about analyzing discourse, language consciousness and integration consciousness. It analyzes political discourse with the help of examples in Uzbek, Kazakh and Russian Languages.